2023
DOI: 10.3389/fnagi.2022.1064667
|View full text |Cite
|
Sign up to set email alerts
|

Progressive structural and covariance connectivity abnormalities in patients with Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) is one of most prevalent neurodegenerative diseases worldwide and characterized by cognitive decline and brain structure atrophy. While studies have reported substantial grey matter atrophy related to progression of AD, it remains unclear about brain regions with progressive grey matter atrophy, covariance connectivity, and the associations with cognitive decline in AD patients.ObjectiveThis study aims to investigate the grey matter atrophy, structural covariance connectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The subcortical regions act as pivotal sensory gates, facilitating the exchange of information with the cortical regions. The previous studies (Cai et al, 2015; Khalilullah et al, 2023; Kim et al, 2023; Lesh et al, 2011; Tentolouris-Piperas et al, 2017; Xiao et al, 2022) also found abnormalities in the psychiatric diseases, particularly for the schizophrenia and Alzheimer’s patients. Our analysis of FNC and mean GM spatial maps (Figure 9c-d) also suggests positive engagement of the caudate nucleus and thalamus with multiple domains.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The subcortical regions act as pivotal sensory gates, facilitating the exchange of information with the cortical regions. The previous studies (Cai et al, 2015; Khalilullah et al, 2023; Kim et al, 2023; Lesh et al, 2011; Tentolouris-Piperas et al, 2017; Xiao et al, 2022) also found abnormalities in the psychiatric diseases, particularly for the schizophrenia and Alzheimer’s patients. Our analysis of FNC and mean GM spatial maps (Figure 9c-d) also suggests positive engagement of the caudate nucleus and thalamus with multiple domains.…”
Section: Discussionmentioning
confidence: 74%
“…In this approach, we observed structural and functional alterations between healthy controls (HCs) and Alzheimer’s disease (AD) patients. Particularly noteworthy patterns in both structural and functional aspects were identified, with a focus on the auditory, visual, subcortical, cognitive control, and cerebellum regions that are recognized as being notably impacted areas for psychiatric disease, particularly for the Alzheimer’s disease (Agosta et al, 2023; Azeem A, 2023; Cai et al, 2015; Cheng et al, 2023; Elvira-Hurtado et al, 2023; Kawabata et al, 2022; Khalilullah et al, 2023; Kim et al, 2023; Lesh et al, 2011; Lin et al, 2017; Liu et al, 2018; Mavroudis, 2019; McEvoy et al, 2023; Sendi et al, 2023; Tang et al, 2021; Tarawneh et al, 2022; Tentolouris-Piperas et al, 2017; Xiao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The human superior temporal gyrus is critical for speech comprehension [ 71 ], while the speech comprehension ability is damaged in AD patients. Significant atrophy of the bilateral superior temporal gyrus in AD patients has been reported in a recent case-control survey [ 72 ]. Our result expands the findings of the observational study and suggests that atrophy of the superior temporal gyrus is a potential causal factor of AD.…”
Section: Discussionmentioning
confidence: 99%
“…There are automated analysis tools to quantify these structural changes, including commercial software (Pemberton et al, 2021), but standard radiology practice continues to rely on qualitative or semi-quantitative methods using visual rating scales (Fazekas et al, 1987;Harper et al, 2015;Scheltens et al, 1995). Advanced MR imaging and analysis have also revealed differences in cerebral blood flow and structural and functional connectivity in patients with cognitive impairment (Liu et al, 2023;Penalba-Sánchez et al, 2023;Teipel & Grothe, 2023;Xiao et al, 2023), but these methods are currently not recommended for memory clinic use since their diagnostic and prognostic value is less established (Egle et al, 2022;Haidar et al, 2023;Vemuri et al, 2012). Thus, our understanding of the links between brain and phenotypic changes is constrained by the data currently available (i.e., cohort studies rather than real-world clinical populations).…”
Section: Introductionmentioning
confidence: 99%